(3OjhGf GHf bdGbSs - (3GHf bdGbS , fUQ Hf YHO Gddg Hf YHO Gdbhj GddNejGdGYR, CHh GdaJhM,J (B567 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO Gddg eSOO SgGe GdacQ dCZQGVgG hGdUdGI Ydi SjOfG eMeO hBdg hUMHg ZjhK GdeOM hQjGVgG aEfj WGdYJ TYQ GdCOjH GdHGQY CHj GdaJM fUQ Hf bdGbS s
(3BNQgG (B:s
(3Sbi GdQGFM GdZGOj VQjMc UhHg hEf cGf jSbj GdQGFMGJ GdZhGOjG hdG HQMJ aj GdbdhH YbjQI JSjd HETQGH GdOeGA GdeGbjG s
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B344s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B182 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B767s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI LGeY GdHGTG HGdehUd (B(12) s
Keywords: (3GdCOHs